Thymosin β4 Regulates Focal Adhesion Formation in Human Melanoma Cells and Affects Their Migration and Invasion - Makowiecka, Aleksandra; Malek, Natalia; Mazurkiewicz, Ewa; Mrówczyńska, Ewa; Nowak, Dorota; Mazur, Antonina Joanna (Frontiers in Cell and Developmental Biology, 2019)
Thymosin β4 (Tβ4), a multifunctional 44-amino acid polypeptide and a member of actin-binding proteins, plays an important role in developmental processes and wound healing. In recent years an increasing number of data has been published suggesting Tβ4’s involvement in tumorigenesis. However, Tβ4’s role in melanoma tumour development still remains to be elucidated. In our study we demonstrate that Tβ4 is crucial for melanoma adhesion and invasion. For the purpose of our research we tested melanoma cell lines differing in invasive potential. Moreover, we applied shRNAs to silence TMSB4X (gene encoding Tβ4) expression in a cell line with high TMSB4X expression. We found out that Tβ4 is not only a component of focal adhesions (FAs) and interacts with several focal adhesions components but also regulates FAs formation. We demonstrate that Tβ4 level has an impact on focal adhesions’ number and morphology. Moreover, manipulation with TMSB4X expression resulted in changes in cells’ motility on non-coated and Matrigel™ (resembling basement membrane composition)-coated surfaces and drastically decreased invasion abilities of the cells. Additionally, a correlation between Tβ4 expression level and exhibition of mesenchymal-like (EMT) features was discovered. Cells with lowered TMSB4X expression were less EMT-progressed than control cells. Summarizing, obtained results show that Tβ4 by regulating melanoma cells’ adhesion has an impact on motility features and EMT. Our study not only contributes to a better understanding of the processes underlying melanoma cells’ capacity to create metastases but also highlights Tβ4 as a potential target for melanoma management therapy